Antibacterial activities of plant-derived xanthones. Issue 2 (12th January 2022) - Liu, Xiaojia; Shen, Jianzhong; Zhu, Kui
Abstract : This review outlines the structures, drug-likeness evaluations and antibacterial activities of plant-derived xanthones. It reveals that natural products isolated from plants may be promising antibacterial candidates. Abstract : The increasing threat to global health posed by antibiotic resistance remains a serious concern. This troublesome scenario has steered a need for the discovery and evaluation of novel antibacterial agents. Natural products are the main sources of antimicrobials used in clinical practice, serving as a rich reservoir for the discovery of new antibiotics. Pharmaceutical phenolics especially xanthones widely exist in the plant kingdom, and are important plant metabolites. They possess versatile biological activities, including antiviral, antibacterial, neurotrophic, and anticancer. In the present study, we focus on the antibacterial activities of phytoxanthones and summarize their structures and sources, categories and drug-likeness evaluations, and antibacterial activities. A total of 226 different plant xanthones are identified through the NETs screening, and most of them are distributed in Clusiaceae family. These phytoxanthones are divided into four groups according to the intrinsic structural properties, including the most common simple xanthones and the majority of biprenylated ones. Moreover, their physicochemical parameters are calculated and the structure–activity relationships are discussed as well. These results indicate that the biprenylated xanthone derivatives may be promising antibacterial candidates and that the natural products of plants may be a poorly understood repository for the discovery of novel antibacterial agents.